1998
DOI: 10.1046/j.1365-2737.1998.00203.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of product-specific variables on consumers' post-consumption behaviour for apparel products: USA

Abstract: Companies spend valuable resources developing and distributing products to please the consumer; however, products that do not match consumer performance expectations during post-purchase use often result in consumer dissatisfaction. This situation can lead to redress-seeking behaviour and negative repurchase behaviour. Understanding factors influencing consumers' post-purchase behaviour can provide retailers with information to make accurate purchasing decisions and improve interpretation of the post-return da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…Product‐specific variables have been shown to be factors in predicting post‐purchase behaviour of some products and consumer services (Kincade et al. , 1998).…”
Section: An Explanation Of Consumer Complaint Behaviourmentioning
confidence: 99%
See 2 more Smart Citations
“…Product‐specific variables have been shown to be factors in predicting post‐purchase behaviour of some products and consumer services (Kincade et al. , 1998).…”
Section: An Explanation Of Consumer Complaint Behaviourmentioning
confidence: 99%
“…Product‐specific variables related to complaint behaviour include: the nature or type of product (product category), cost of the product (Kincade et al. , 1998; Stephens and Gwinner, 1998), durability (Day and Landon, 1977, p. 434; Kincade et al. , 1998), importance of the product to the consumer (Stephens and Gwinner, 1998; Sheth et al.…”
Section: An Explanation Of Consumer Complaint Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Day (1977) suggested that researchers need to collect data on a product-by-product basis for the study of CS/D. Studies indicated that consumers consistently experience dissatisfaction with apparel products, and this product category caused greater consumer dissatisfaction than many other major product categories (Engel & Blackwell, 1982;Huefner & Hunt, 1992;Kincade, Giddings, & Chen-Yu, 1998). Apparel is one product category where a better understanding of CS/D is needed.…”
mentioning
confidence: 99%
“…Some studies have examined products within a specific category (e.g. apparel) 38–40 . Among the first to empirically study e‐satisfaction, Ho and Wu 41 suggested several antecedents of customer satisfaction while shopping in an online environment including logistical support, technological characteristics, information characteristics, homepage presentation, and product characteristics.…”
Section: Review Of Literaturementioning
confidence: 99%